(untitled) (शोधसुधा Shodh Sudha, 2023)
The research paper aims to analyse the cost and revenue of bakery industry in Dharan. This research is based on primary data. To achieve the objective, quantitative and qualitative research designs have been used. Bakery industry is the emerging business industry in Dharan. Bakery industry is a huge business that caters to people’s weaknesses for tasty breads, cakes, pies and sweet rolls. It is revealed that the cost and revenue of bakery products have highest mean values whereas location is least important than other dimensions. There is various bakery industry in Dharan, which produce different types of Bakery products and it provides various job opportunities. Lack of skilled manpower, scarcity of water, sufficient amount of food product are major problems of bakery industry and high price of raw material is another major problem of bakery industry in Dharan.